2019
DOI: 10.1139/cjpp-2019-0131
|View full text |Cite
|
Sign up to set email alerts
|

3-Bromopyruvate potentiates TRAIL-induced apoptosis in human colon cancer cells through a reactive oxygen species- and caspase-dependent mitochondrial pathway

Abstract: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is a promising anticancer cytokine with minimal toxicity towards normal cells. Nevertheless, most primary cancers are often intrinsically TRAIL-resistant or can acquire resistance after TRAIL therapy. This study aimed to investigate the inhibitory effect of co-treatment of 3-bromopyruvate (3-BP) as a potent anticancer agent with TRAIL on colon cancer cells (HT-29). The results of present study indicated that combined treatment with 3-BP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…2-Deoxy-D-glucose (2-DG) is an analog of glucose that has recently been used as an HK inhibitor because it can be phosphorylated by HKs but not catalyzed further [117]. Another small molecule, 3-bromopyruvate (3-BP), and the novel agent methyl jasmonate (MJ) can suppress glycolysis and cancer growth in cancer patients [118,119]. It was concluded that the lncRNA hox transcript antisense RNA (HOTAIR) is tightly linked with HK2 in PDAC patients.…”
Section: Pivotal Enzymes In Glycolysismentioning
confidence: 99%
“…2-Deoxy-D-glucose (2-DG) is an analog of glucose that has recently been used as an HK inhibitor because it can be phosphorylated by HKs but not catalyzed further [117]. Another small molecule, 3-bromopyruvate (3-BP), and the novel agent methyl jasmonate (MJ) can suppress glycolysis and cancer growth in cancer patients [118,119]. It was concluded that the lncRNA hox transcript antisense RNA (HOTAIR) is tightly linked with HK2 in PDAC patients.…”
Section: Pivotal Enzymes In Glycolysismentioning
confidence: 99%
“…4B and C ). Since caspase-9 is activated by Bcl-2 family proteins ( 36 ), it was investigated whether 20(S)-GRh2 affected the expression of Bcl-2 and Bax proteins. 45 µ M 20(S)-GRh2 induced Bax upregulation and Bcl-2 downregulation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, numerous studies have focused on the finding new anticancer agents with high efficacy and low toxicity (Pucci, Martinelli, & Ciofani, 2019). In this sense, flavonoids have attracted much attention owing to their potent antiproliferative effects with minimal toxicity against healthy tissues (Abbaszadeh, Ebrahimi, & Akhavan, 2014;Abbaszadeh, Valizadeh, et al, 2019). Therefore, flavonoids have the potential to be developed as promising chemopreventive and anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have explored that one of the most significant drawbacks of flavonoids is their very low bioavailability that restricts their clinical use. The poor bioavailability of flavonoids is mainly attributed to their poor watersolubility (Abbaszadeh, Valizadeh, et al, 2019). Morin, as a dietary flavonoid with significant anticarcinogenic and anticancer effects, has been found to have a poor bioavailability, which is associated with its strategies have been employed to improve the oral bioavailability of morin (Choi et al, 2015;Ikeuchi-Takahashi et al, 2016;Zhang et al, 2011;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation